The Problem of Integrating Russian Scientific And Technical Information Resources into The Global Information Space - Viktoriia LAPOCHKINA; Elena PLEKHANOVA; Viktor BOGATOV; Konstantin DIKUSAR; Karina BORODIK (Communications of International Proceedings, 2021)
The need to ascertain the problems of integrating Russian scientific and technical information resources into the global information space and the search for ways to solve these problems is topical as the research results of Russian scientists need to be promoted both in Russian and international publications. In our opinion, previously carried out studies of the evolution of the mechanisms and tools being used to stimulate the integration processes into the global information space in the field of scientific and technical information do not provide a complete and objective picture because they have not considered all the aspects of integration, which is rapidly developing in the modern era of digitalization and globalization. The authors of this study tried to develop the definitions of scientific and technical information, scientific and technical information resources, analyzed the regulatory and legal framework of the scientific and technical information system, assessed approaches to the organization of such information and the recording of its usage, proposed directions for the growth of integration processes in the field of scientific and research activities and the creation of efficient tools for integrating Russian scientific and technical information resources into the global information space.
Keywords: Scientific and Technical Information; Integration; Scientometric; Government of Science.